PENGARUH MODEL PEMBELAJARAN DOUBLE LOOP PROBLEM SOLVING (DLPS) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA MATA PELAJARAN FIKIH KELAS X MAN 1 BONE - Fatrika, Fifi; Yahya, M; Zubaedy, M (IAIN Bone, 2023)
Abstract This study examines the impact of the Double Loop Problem Solving(DLPS) learning model on student learning outcomes in the scienceclass X at MAN 1 Bone. The primary objective of this research is toassess the influence of implementing the Double Loop ProblemSolving (DLPS) learning model on student learning outcomes in thefiqh class X at MAN 1 Bone. The research follows a quantitativeapproach, utilizing pedagogic methodology, and employs datacollection techniques such as tests and documentation. The study'sresearch design adopts a Quasi-Experimental approach, utilizingthe Nonequivalent Control Group Design research plan. Thefindings indicate a notable effect of the Double Loop ProblemSolving (DLPS) learning model on the learning outcomes of studentsin the fiqh class at Madrasah Aliyah Negeri (MAN) 1 Bone.Specifically, the Double Loop Problem Solving (DLPS) learningmodel proves to be more suitable for use in fiqh lessons,particularly when teaching ownership material in Islamic contracts,as compared to the conventional lecture learning model.Keywords: Double Loop Problem Solving Learning Model (DLPS),Learning Outcomes, fiqhÂ